Education for Sustainable Development in Science National Exam Questions of Elementary School - Lilis Suryani; Ghullam Hamdu (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study is to describe the theme of Education for Sustainable Development (ESD) and the system thinking skills set out in the 2016-2018 National Science Examination Questions for Elementary Schools. This study uses qualitative research with content analysis methods presented through descriptive delivery techniques. The results of this study indicate that the average result of the highest percentage of ESD theme content on the 2016-2018 Elementary School National Science Examination questions is on biodiversity subject as many as 52.2%, while the average result is the highest percentage of systems thinking competency on the exam questions. 65.9% of the National Science Elementary School from 2016 to 2018 is in the ability to perform complex analysis because students are asked more questions on the plants and animals body parts shape and function; type of animal; ecosystem components; how living things conform; and natural resources. Also, students are given more questions in system component analysis.